Harnessing of urease activity of Helicobacter pylori to induce self-destruction of the bacterium. - Greig, M A (1991)
Eradication of Helicobacter pylori with currently available antibacterial agents is unsatisfactory due to the risk of side-effects and the emergence of resistance. The organism rapidly dies in vitro in the presence of urea at pH 6. When incubated in citrate buffer (pH 6) plus urea (10 mM) the five minute survival was 26% compared with 96% without urea and the survival progressively decreased with increasing urea concentrations, being only 9% in 50 mM urea. The bactericidal effect depended on pH as the organism survived in citrate buffer (pH 7) plus urea (50 mM). The death of the organism at pH 6 in the presence of urea was prevented by the addition of the competitive urease inhibitor hydroxyurea. These findings indicate that destruction of the organism is mediated by its exceptionally high urease activity. Harnessing this enzyme to induce self-destruction could provide a new approach to eradicating this common infection.